From Privilege to Competition : Unlocking Private-Led Growth in the Middle East and North Africa - World Bank (Washington, DC, 2013)
The report starts with an introductory chapter that sets the stage for the issues and provides a short historical background on the development of the private sector in Middle East and North Africa (MENA), drawing on anecdotes and stories heard from many entrepreneurs and public officials consulted throughout the region during the preparation of this report. The core of the analysis is then presented in three parts. Part one assesses the performance of private sector development in the region from a macroeconomic and microeconomic standpoint (chapter two). It then presents the framework that is used to explain the identified performance gap (chapter three) and uses this framework in (chapter four) to claim that the lack of private sector dynamism in MENA is not necessarily due to insufficient reforms, but rather to the discretionary way in which rules and policies are implemented, and the lack of credibility of governments to really level the playing field when applying their policies and reforms. Part two then illustrates how this issue of poor implementation of the policies translates in three key policy areas in the business environment of the region: access to finance (chapter five), access to land (chapter six), and the conduct of industrial policies (chapter seven). The aim is to show how the role of the state and its institutions, when diverted from their regulatory and administrative missions by special interests and when subject to discretionary influence, can distort policies that may otherwise be well designed and well intended. Part three analyzes the political economy of reforms in MENA (chapter eight) and uses this analysis to offer a set of strategic recommendations and concrete policy actions that take into account the region's diversity and political economy (chapter nine).